MONITORING MECHANISM DAN CREATED SHAREHOLDER VALUE PERUSAHAAN PUBLIK DI INDONESIA - Sutaryo . (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2013)
This study investigates the influence of corporate control mechanisms on the created shareholder value in publicly traded companies in Indonesia. The oversight mechanisms tested in this study are internal monitoring mechanism and external monitoring mechanisms. This study found that the mechanism of both internal and external oversight affects the created shareholder value of companies in Indonesia. These results indicate that corporate governance is a mechanism run by a company in Indonesia to increase shareholder value. Thus, investors and other users of financial statement information can use this monitoring mechanism in economic decision-making in order to optimize the goals of the decision.Keywords: corporate control, created shareholder value, internal monitoring, external monitoring.